Hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor as well as preparation method and application thereof

Through the use of hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor, the serious local corrosion problem in high H2S and CO2 environments is solved, and a non-toxic, green and efficient steel corrosion inhibition effect is achieved. It is suitable for anti-corrosion of pipeline steel in acidic environments such as petroleum.

CN119553284APending Publication Date: 2025-03-04JIANGSU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411751125.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the process of oil and gas resource exploitation with high H2S and CO2, local corrosion phenomenon is serious, and existing organic corrosion inhibitors are highly toxic, and they are harmful to the environment and the human body after compounding. It is necessary to develop more efficient and environmentally friendly metal corrosion inhibitors.

Method used

The compound corrosion inhibitor is used to combine hydroxyphosphonic acid-zinc gluconate with zinc gluconate, which forms a precipitated film corrosion inhibitor by combining zinc gluconate with hydroxyphosphonic acid, and combines hydroxyphosphonic acid with good chemical stability and hydrolysis resistance to significantly improve the anti-corrosion effect.

Benefits of technology

A non-toxic, green and efficient environmentally friendly steel corrosion inhibitor is achieved. The corrosion inhibitor after compounding is improved by 1.5 times, and it can effectively prevent corrosion of pipeline steel in acidic environments rich in petroleum and other acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553284A_ABST
    Figure CN119553284A_ABST
Patent Text Reader

Abstract

The invention discloses a hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor as well as a preparation method and application thereof. Each liter of the corrosion inhibitor comprises the following raw materials: 100mg / L of hydroxyphosphonic acid, 2-20mg / L of zinc gluconate and the balance of water. According to the hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor, zinc gluconate and hydroxyphosphonic acid are compounded to achieve a corrosion inhibition synergistic effect, the hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor is a non-toxic, green and efficient environment-friendly steel corrosion inhibitor, the corrosion inhibition energy can be effectively improved, the preparation method and the use process of the corrosion inhibitor are simple, the corrosion inhibition effect is good, the production cost is low, and the corrosion inhibitor is suitable for industrial production. The corrosion inhibitor is stable and convenient to store and produce in a large scale, and has extremely high practical application value, and a layer of protective film can be generated on the surface of the steel treated by the corrosion inhibitor, so that further corrosion is efficiently prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a compound corrosion inhibitor, in particular to a hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor, and also to a preparation method and application of the compound corrosion inhibitor. Background Art

[0002] Hydrogen sulfide (HS) is one of the most common corrosive substances in oil and gas pipelines. It is known to accelerate the hydrotreating reaction, leading to a decrease in plasticity, thereby accelerating the corrosion rate of pipeline steel. Various organic inhibitors have been reported to reduce the corrosion rate of pipeline steel in acidic H2S solutions. The main features of these inhibitors include multi-bonded structures and heteroatoms such as oxygen, phosphorus, nitrogen, and sulfur. These inhibitors adsorb on the metal surface, forming a protective layer at the molecular level and helping to prevent the dissolution of the metal in the electrolyte solution. Under acidic conditions, the heteroatoms present in the polar functional groups of these inhibitors can affect the anodic / cathodic reactions, thereby successfully slowing down their progress. In addition, these heteroatoms, after protonation in an acidic environment, promote the adsorption of the inhibitors and form a molecular layer on the metal surface. The interaction between the paired electrons of this organic inhibitor and the empty d orbitals of the metal enhances the adsorption process by acting as an electron acceptor-donor pair.

[0003] Conventional metal corrosion inhibitors mostly use chemical additives that pose a serious threat to the natural environment and health, so the future development trend of this field will focus more on the development of environmentally friendly metal corrosion inhibitors. Current research shows that compared with a single corrosion inhibitor, the corrosion inhibition rate of the compounded corrosion inhibitor will be significantly improved. Many corrosion inhibitors and synergists will produce corrosion inhibition synergistic effects under specific conditions, such as the corrosion inhibition synergistic system of organic matter and halogen ions, the corrosion inhibition synergistic system of organic matter and other ions, the corrosion inhibition synergistic system of organic matter and surfactants, the corrosion inhibition synergistic system between organic matter, the corrosion inhibition synergistic system of inorganic salts, and the corrosion inhibition synergistic system of plant-based corrosion inhibitors. For many years, the research on the synergistic effect of corrosion inhibitors has focused on neutral systems, while relatively few studies have been conducted under more severe corrosion conditions. For example, in the process of oil and gas resource exploitation with high H2S and CO2 content, local corrosion is very serious, and perforation, fracture and even explosion and other malicious events occur from time to time. At the same time, most organic corrosion inhibitors are highly toxic and may cause great harm to the environment and human body after compounding. Therefore, it is necessary to develop more efficient and environmentally friendly metal corrosion inhibitors that can operate in harsh environments. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a non-toxic, green and highly efficient environmentally friendly hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor, and also to provide a method for preparing the above-mentioned compound corrosion inhibitor and its application in the corrosion protection of pipeline steel in an acidic environment such as one rich in petroleum.

[0005] Technical solution: The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the present invention comprises the following raw materials per liter: 100 mg / L hydroxyphosphonic acid, 2-20 mg / L zinc gluconate, and the balance is water.

[0006] Wherein, the pH value of the compound corrosion inhibitor is 7-8.

[0007] Wherein, the water is deionized water.

[0008] The preparation method of the above-mentioned composite corrosion inhibitor comprises the following steps:

[0009] (1) taking 50-70% of the volume of water to prepare the target corrosion inhibitor, adding hydroxyphosphoric acid and zinc gluconate and stirring evenly until completely dissolved to obtain a mixed solution;

[0010] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0011] Among them, the configuration control temperature is 293~323K.

[0012] The above-mentioned hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor can also be used for corrosion protection of pipeline steel in acidic environments such as those rich in petroleum.

[0013] Among them, the concentration ratio of the corrosive liquid in the pipeline steel to the corrosion inhibitor is 1:1.5~2.

[0014] Among them, it is preferably used in a corrosive environment of hydrogen sulfide.

[0015] Among them, the application is to use a compound corrosion inhibitor to form a protective film on the inner surface of the pipeline steel to hinder corrosion in the acidic environment.

[0016] Specifically, the application is to configure a composite corrosion inhibitor for pipeline steel according to the concentration of corrosive liquid in the oil pipeline, and use a pipeline corrosion inhibitor plug to cover the composite corrosion inhibitor for pipeline steel on the inner surface of the pipeline under the push of gas.

[0017] Principle of the invention: The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the present invention takes zinc gluconate as the core corrosion inhibition component and is compounded with hydroxyphosphonic acid (HPAA), wherein the precipitation film type corrosion inhibitor zinc gluconate (ZnGL) forms a Zn(OH)2 precipitation film in the local alkaline environment of the cathode to prevent oxygen from diffusing to the metal surface, thereby playing a protective role, combined with the organic acid hydroxyphosphonic acid (HPAA) with good chemical stability and hydrolysis resistance, its structure contains a carboxyl group, which significantly improves the anti-corrosion effect, and its phosphorus content is low, which can increase the solubility of zinc salts.

[0018] The working principle of the corrosion inhibitor of the present invention is that HPAA and Zn +It combines with the metal surface to produce adsorption, thereby hindering the corrosion process of the metal surface to achieve the effect of corrosion inhibition. Among them, zinc gluconate (ZnGL) can be used as a corrosion inhibitor for pipeline steel when exposed to hydrogen sulfide (H2S) in a simulated corrosion solution. At the same time, the introduction of organic phosphonic acid, namely hydroxyphosphonic acid (HPAA), further synergistically improves the inhibition efficiency. The addition of HPAA to the ZnGL solution not only promotes the precipitation of Zn(OH)2, but also helps proton dissociation, resulting in the production of negatively charged phosphorus. These substances can easily react with Fe 2+ and Zn 2+ The polymer is formed to form a protective film on the metal surface and is absorbed and released to the surface of iron. The synergistic effect between HPAA and ZnGL is mainly attributed to the co-adsorption of their molecules on the steel surface, thus highlighting the nature of their synergistic effect. The study of these systems provides a new idea for metal inhibitors in acidic pipeline environments. Therefore, the combination of hydroxyphosphoric acid and zinc gluconate can effectively improve the corrosion inhibition ability, and there is a synergistic effect of corrosion inhibition between the two.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the present invention achieves a synergistic corrosion inhibition effect by compounding zinc gluconate and hydroxyphosphonic acid, is a non-toxic, green and efficient environmentally friendly steel corrosion inhibitor, and can effectively improve the corrosion inhibition ability. The corrosion inhibition efficiency of the composite corrosion inhibitor is increased by 1.5 times compared with that before compounding; (2) The preparation method and use process of the corrosion inhibitor of the present invention are simple, the corrosion inhibition effect is good, the production cost is low, the corrosion inhibitor is stable, and it is easy to store and mass produce. It has extremely high practical application value. After being treated with the corrosion inhibitor, a protective film will be generated on the surface of the steel, which effectively prevents the further occurrence of corrosion. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the polarization curve of X65MS pipeline steel in hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor;

[0021] Figure 2 This is the impedance diagram of X65MS pipeline steel in hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor;

[0022] Figure 3 Polarization curves of X65MS pipeline steel with hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor at different temperatures;

[0023] Figure 4 Impedance diagram of X65MS pipeline steel with hydroxyphosphonic acid-zinc gluconate compound corrosion inhibitor at different temperatures;

[0024] Figure 5 Polarization curves of X65MS pipeline steel in different concentrations of zinc gluconate corrosion inhibitor;

[0025] Figure 6 The impedance diagram of X65MS pipeline steel in different concentrations of zinc gluconate corrosion inhibitor;

[0026] Figure 7 The graph shows the c / θ and c curves of hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitors with different concentrations. DETAILED DESCRIPTION

[0027] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.

[0028] Example 1

[0029] The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the invention comprises the following raw materials: hydroxyphosphonic acid, zinc gluconate and water; the dosage thereof is 100 mg / L of hydroxyphosphonic acid, 2 mg / L of zinc gluconate, and the rest is water.

[0030] The preparation method of 100 ml of corrosion inhibitor specifically includes the following steps:

[0031] (1) Take 70% of the volume of water containing the target corrosion inhibitor, add 10 mg of hydroxyphosphoric acid and 0.2 mg of zinc gluconate, and stir evenly at a temperature of 303 K until completely dissolved to obtain a mixed solution;

[0032] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0033] Example 2

[0034] The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the invention comprises the following raw materials: hydroxyphosphonic acid, zinc gluconate and water; the dosage thereof is 100 mg / L of hydroxyphosphonic acid, 8 mg / L of zinc gluconate, and the rest is water.

[0035] The preparation method of 100 ml of corrosion inhibitor specifically includes the following steps:

[0036] (1) Take 50% of the volume of water containing the target corrosion inhibitor, add 10 mg of hydroxyphosphoric acid and 0.88 mg of zinc gluconate, and stir evenly at a temperature of 303 K until completely dissolved to obtain a mixed solution;

[0037] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0038] Example 3

[0039] The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the present invention comprises the following raw materials: hydroxyphosphonic acid, zinc gluconate and water; the dosage thereof is 100 mg / L hydroxyphosphonic acid, 20 mg / L zinc gluconate, and the rest is water, 20 mg / L ZnGL+100 mg / L HPAA (303K).

[0040] The preparation method of 100 ml of corrosion inhibitor specifically includes the following steps:

[0041] (1) Take 70% of the volume of water containing the target corrosion inhibitor, add 10 mg of hydroxyphosphoric acid and 2 mg of zinc gluconate, and stir evenly at a temperature of 303 K until completely dissolved to obtain a mixed solution;

[0042] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0043] Verify the application of the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor prepared in Examples 1 to 3:

[0044] (1) Take 4 beakers of the same size and add 50 ml of 3.5 wt% NaCl + 0.005 mol / L Na2S2O3 solution to obtain a simulated sample of the acidic corrosive solution;

[0045] (2) Add 50 ml of the prepared 20 mg / L zinc gluconate and 100 mg / L hydroxyphosphonic acid solution to the simulated sample of the acidic corrosive solution obtained in step (1), stir evenly until completely dissolved to obtain a mixed solution, and measure the pH with a Cantonese pH test paper to verify that the pH value of the obtained solution is about 5, which is close to acidity.

[0046] Verification of the corrosion inhibition effect of the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor prepared in Examples 1 to 3:

[0047] The method of using the steel corrosion inhibitor obtained in the embodiment is that the electrode material is X65MS steel, and the X65MS pipeline steel is machined into a sample with an outer size of 10mm×10mm×5mm. The wire is welded to the back of the working surface of the sample with tin liquid, the sample is placed therein and sealed with epoxy resin; then, the working surface of the X65MS pipeline steel is polished step by step with 400#-2000# sandpaper until the surface is smooth. The polished sample is cleaned with anhydrous ethanol and deionized water, degreased with acetone, and dried with cold air for standby use. A three-electrode system is used for measurement, the research electrode is X65MS pipeline steel, the reference electrode is a silver chloride electrode, and the auxiliary electrode is a platinum electrode. The research electrodes are immersed in the corrosion inhibitor with or without HPAA, and the three-electrode system is formed with a saturated silver chloride electrode and a platinum electrode for electrochemical testing. The scanning speed is 0.5mV / s when measuring the steady-state polarization curve, and the scanning range is -300 to 300mV relative to the open circuit potential. The electrode potentials are all relative to the silver chloride electrode potential. The AC impedance spectrum measurement frequency range is 10 -2 ~10 5 Hz, AC excitation signal amplitude 5mV. Experimental temperature was controlled at about 303K.

[0048] Polarization curves and impedance results of X65MS pipeline steel samples in HPAA corrosion inhibitors with different concentrations of zinc gluconate added, such as Figure 1 and Figure 2 As shown, the fitting parameters are shown in Table 1. When the ZnGL concentration in the compound corrosion inhibitor is 2 mg / L, the inhibition efficiency is about 63%. As the concentration of the compound corrosion inhibitor increases, the inhibition efficiency gradually increases. When the ZnGL addition in the compound corrosion inhibitor is 20 mg / L, the combination of ZnGL and HPAA significantly reduces the anodic and cathodic reactions, resulting in a decrease in the corrosion current density and an inhibition efficiency of 89.91%. Relative to the saturated thermal mass electrode, the inhibitory effect of HPAA on the anodic dissolution reaction is obvious in the anodic curve at a potential exceeding 600 mV. This potential is often referred to as the desorption potential, which indicates that the inhibition mode imposed by the inhibitor depends on the electrode potential. This behavior may be due to the significant dissolution of iron from the steel, resulting in the separation of the inhibitor layer from the metal surface. In this case, the rate of inhibitor desorption exceeds its adsorption rate.

[0049] Table 1. Fitting parameters of X65MS pipeline steel in hydroxyphosphoric acid-zinc gluconate corrosion inhibitor

[0050]

[0051] From the impedance graph, it can be seen that the diameter of the semicircle increases with the increase of the amount of ZnGL added. After adding 2mg / L ZnGL, the charge transfer resistance of the blank solution and 2mg / L ZnGL+100mg / L HPAA solution increased from 260 to 740.32Ωcm2 , and then increased to 2578Ωcm after adding 20mg / L ZnGL 2 In addition, after adding 20mg / L ZnGL+100mg / L HPAA, the double layer capacitance increased from 5.234×10 -7 Down to 7615×10 -7 F -2 , while the inhibition efficiency increased from 63.07% to 89.91%, thus correlating with the polarization results. This enhancement of the inhibition efficiency in the presence of HPAA by the addition of ZnGL can be attributed to a synergistic effect.

[0052] Example 4

[0053] The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the invention comprises the following raw materials: hydroxyphosphonic acid, zinc gluconate and water; the dosage is 100 mg / L hydroxyphosphonic acid, 20 mg / L zinc gluconate, and the rest is water; 20 mg / L ZnGL+100 mg / L HPAA (293K).

[0054] 100 ml of corrosion inhibitor was prepared. The preparation method was changed to 293 K compared with Example 3, and specifically included the following steps:

[0055] (1) Take 70% of the volume of water containing the target corrosion inhibitor, add 10 mg of hydroxyphosphoric acid and 2 mg of zinc gluconate, and stir evenly at a temperature of 293 K until completely dissolved to obtain a mixed solution;

[0056] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0057] Example 5

[0058] The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the invention comprises the following raw materials: hydroxyphosphonic acid, zinc gluconate and water; the dosage is 100 mg / L hydroxyphosphonic acid, 20 mg / L zinc gluconate, and the rest is water; 20 mg / L ZnGL+100 mg / L HPAA (313K).

[0059] 100 ml of corrosion inhibitor was prepared. The preparation method thereof was compared with that in Example 3, except that the temperature was changed to 313 K. The preparation method specifically comprised the following steps:

[0060] (1) Take 70% of the volume of water containing the target corrosion inhibitor, add 10 mg of hydroxyphosphoric acid and 2 mg of zinc gluconate, and stir evenly at a temperature of 313 K until completely dissolved to obtain a mixed solution;

[0061] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0062] Example 6

[0063] The hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the present invention comprises the following raw materials: hydroxyphosphonic acid, zinc gluconate and water; the dosage is 100 mg / L hydroxyphosphonic acid, 20 mg / L zinc gluconate, and the rest is water; 20 mg / L ZnGL+100 mg / L HPAA (323K).

[0064] 100 ml of corrosion inhibitor was prepared. The preparation method thereof was compared with that in Example 4, except that the temperature was changed to 323 K. The preparation method specifically comprised the following steps:

[0065] (1) Take 70% of the volume of water containing the target corrosion inhibitor, add 10 mg of hydroxyphosphoric acid and 2 mg of zinc gluconate, and stir evenly at a temperature of 323 K until completely dissolved to obtain a mixed solution;

[0066] (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

[0067] Verify the application of the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor prepared in Examples 3 to 4:

[0068] (1) Take 4 beakers of the same size and add 50 ml of 3.5 wt% NaCl + 0.005 mol / L Na2S2O3 solution to obtain a simulated sample of the acidic corrosive solution;

[0069] (2) Add 50 ml of the prepared 20 mg / L zinc gluconate and 100 mg / L hydroxyphosphonic acid solution to the simulated sample of the acidic corrosive solution obtained in step (1), stir evenly until completely dissolved to obtain a mixed solution, and measure the pH with a Cantonese pH test paper to verify that the pH value of the obtained solution is about 5, which is close to acidity.

[0070] Verification of the corrosion inhibition effect of the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor prepared in Examples 3 to 6:

[0071] The method for using the steel corrosion inhibitor obtained in this embodiment is that the electrode material is X65MS steel, and the X65MS pipeline steel is machined into a sample with an outer size of 10mm×10mm×5mm. The wire is welded to the back of the working surface of the sample with tin liquid, and the sample is placed therein and sealed with epoxy resin; then, the working surface of the X65MS pipeline steel is polished step by step with 400#-2000# sandpaper until the surface is smooth. The polished sample is cleaned with anhydrous ethanol and deionized water, degreased with acetone, and dried with cold air for standby use. A three-electrode system is used for measurement, the research electrode is X65MS pipeline steel, the reference electrode is a silver chloride electrode, and the auxiliary electrode is a platinum electrode. The research electrodes are immersed in ZnGL+HPAA corrosion inhibitors at different temperatures, and a three-electrode system is formed with a saturated silver chloride electrode and a platinum electrode for electrochemical testing. The scanning speed is 0.5mV / s when measuring the steady-state polarization curve, and the scanning range is -300 to 300mV relative to the open circuit potential. The electrode potentials are all relative to the silver chloride electrode potential. The AC impedance spectrum measurement frequency range is 10 -2 ~10 5 Hz, AC excitation signal amplitude 5mV.

[0072] The polarization curves and impedance diagrams of the X65MS pipeline steel samples obtained in Examples 3 to 6 in the ZnGL+HPAA corrosion inhibitor at different temperatures are shown in FIG. Figure 3 and Figure 4 The obtained fitting parameters are shown in Table 2.

[0073] Table 2. Fitting parameters of X65MS pipeline steel in corrosion inhibitor at different temperatures

[0074]

[0075] The results show that after adding these corrosion inhibitors, i corr It decreases with increasing temperature, indicating that the corrosion rate of X65MS pipeline steel in the simulated hydrogen sulfide corrosion solution decreases with increasing temperature. This result confirms that ZnGL and HPAA corrosion inhibitors exhibit good corrosion inhibition performance even at high temperatures. At the same time, in the presence of ZnGL and HPAA corrosion inhibitors, the impedance value increases significantly. This shows that although the increase in temperature accelerates the corrosion rate, these inhibitors prevent corrosion by forming an adsorption film on the interface, effectively inhibiting the charge transfer process. Importantly, the EIS results are consistent with the polarization measurement results. It can be seen that the inhibitors of the present invention have potential for application in a wide range of industrial processes at moderately high temperatures.

[0076] Comparative Example 1

[0077] A zinc gluconate corrosion inhibitor, the components and contents of which are: 2, 8 and 20 mg / L of zinc gluconate respectively, and the rest being water.

[0078] Verification of the application of zinc gluconate corrosion inhibitor in comparative example 1:

[0079] (1) Take 4 beakers of the same size and add 50 ml of 3.5 wt% NaCl + 0.005 mol / L Na2S2O3 solution to obtain a simulated sample of the acidic corrosive solution;

[0080] (2) Add 50 ml of the prepared 2, 8, and 20 mg / L zinc gluconate solutions to the simulated sample of the acidic corrosive solution obtained in step (1), respectively, stir evenly until completely dissolved to obtain a mixed solution, and measure the pH with a Cantonese pH test paper to verify that the pH value of the obtained solution is about 7, which is close to neutral.

[0081] Verify the corrosion inhibition effect of the comparative corrosion inhibitor:

[0082] The method for using the steel corrosion inhibitor obtained in this embodiment is that the electrode material is X65MS steel, and the X65MS pipeline steel is machined into a sample with an outer size of 10mm×10mm×5mm. The wire is welded to the back of the working surface of the sample with tin liquid, and the sample is placed therein and sealed with epoxy resin; then, the working surface of the X65MS pipeline steel is polished step by step with 400#-2000# sandpaper until the surface is smooth. The polished sample is cleaned with anhydrous ethanol and deionized water, degreased with acetone, and dried with cold air for standby use. A three-electrode system is used for measurement, the research electrode is X65MS pipeline steel, the reference electrode is a silver chloride electrode, and the auxiliary electrode is a platinum electrode. The research electrodes are immersed in ZnGL+HPAA corrosion inhibitors at different temperatures, and a three-electrode system is formed with a saturated silver chloride electrode and a platinum electrode for electrochemical testing. The scanning speed is 0.5mV / s when measuring the steady-state polarization curve, and the scanning range is -300 to 300mV relative to the open circuit potential. The electrode potentials are all relative to the silver chloride electrode potential. The AC impedance spectrum measurement frequency range is 10 -2 ~10 5 Hz, AC excitation signal amplitude 5mV.

[0083] Table 3. Fitting parameters of X65MS pipeline steel in different concentrations of zinc gluconate inhibitor

[0084]

[0085] The polarization curves and impedance of the X65MS pipeline steel samples obtained in this example in different concentrations of zinc gluconate inhibitor are as follows: Figure 5 and Figure 6 The obtained fitting parameters are shown in Table 3. It can be seen from the data in the table that after adding ZnGL concentration to 2 mg / L, the corrosion current is 3.948 μA / cm 2 Reduced to 1.592μA / cm 2, and with the increase of agent concentration, the corrosion current decreases more significantly. At the same time, it can be seen from the significant decrease in βc value that ZnGL mainly controls the cathode hydrogen evolution reaction. This is because Zn 2+ A Zn(OH)2 precipitation film is formed in the local alkaline environment of the cathode to prevent carbon steel from contacting with corrosive ions. According to the changes in βa and Ecorr, ZnGL is a mixed corrosion inhibitor that mainly controls the cathode. It may be that the adsorption of gluconate restricts the diffusion of the anode area to interfere with the anode process. In addition, after adding ZnGL to a concentration of 2 mg / L, the charge transfer resistance R ct The corrosion current is 260Ωcm compared with the blank test 2 Rising to 394.2Ωcm 2 , and with the increase of the concentration of the agent, the increase of the transfer resistance is more obvious. At the same time, with the increase of the concentration of ZnGL, C dl The C value was decreased after adding ZnGL to the acidic solution. dl The decrease in ZnGL indicates that a protective layer has formed on the electrode surface, replacing any water molecules that may be present. As the ZnGL concentration increases, the thickness of the protective layer and the coverage of ZnGL also increase, which may be due to the increased electrostatic adsorption of ZnGL on the electrode surface. When the ZnGL concentration is 20 mg / L, the corrosion inhibition rate reaches the highest 60.02%.

[0086] Verify the mutual adsorption between zinc gluconate and hydroxyphosphonic acid HPAA:

[0087] The Langmuir adsorption isotherm is used to calculate the adsorption information on the steel surface. Figure 7 As shown, r 2 is close to 1. This indicates that the adsorption of HPAA-ZnGL on the pipe steel surface is consistent with the Langmuir monolayer adsorption. The Langmuir adsorption isotherms of c and c / θ produce an intercept of 1 / K ads The Langmuir adsorption isotherm formula is:

[0088]

[0089] Where K ads is the adsorption equilibrium constant, c is the inhibition concentration, and θ is the surface coverage after corrosion inhibition. Therefore, the adsorption free energy

[0090]

[0091] Depend on Figure 7 It can be seen that the adsorption equilibrium constant (K ads ) is 1.4329×10 4, indicating that the ZnGL+HPAA composite corrosion inhibitor has a strong adsorption capacity. The Gibbs free energy in the adsorption process was calculated according to the equation, and its negative value was -34.23kJ / mol (absolute value = 20-40kJ / mol). The results show that the adsorption behavior of HPAA-ZnGL is not only physical adsorption by intermolecular force attraction, but also chemical adsorption charge transfer and shared covalent bonds, but its absolute value is close to 40kJ / mol, indicating that chemical adsorption plays a dominant role. Therefore, it can be proved that there is an adsorption relationship between HPAA and zinc gluconate. Zinc gluconate and HPAA combine to form a dense adsorption layer on the metal surface, which prevents the dissolution of Fe. This layer reduces the corrosion rate, effectively hinders the corrosion of the metal, and has a significant inhibitory effect. More specifically, the hydroxyl group of HPAA enhances the adsorption of zinc gluconate molecules on the surface of pipeline steel, promotes the generation of Zn(OH)2, and ultimately reduces the corrosion level.

[0092] Therefore, the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor of the present invention achieves a synergistic corrosion inhibition effect, is a non-toxic, green and efficient environmentally friendly steel corrosion inhibitor, is easy to store and mass produce, and has extremely high practical application value.

Claims

1. A hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor, characterized in that: The corrosion inhibitor comprises the following raw materials per liter: 100 mg / L of hydroxyphosphonic acid, 2-20 mg / L of zinc gluconate, and the balance is water.

2. The composite corrosion inhibitor according to claim 1, characterized in that The pH value of the compound corrosion inhibitor is 7-8.

3. The composite corrosion inhibitor according to claim 1, characterized in that The water is deionized water.

4. A method for preparing the composite corrosion inhibitor according to claim 1, characterized in that: The following steps are involved: (1) taking 50-70% of the volume of water to prepare the target corrosion inhibitor, adding hydroxyphosphoric acid and zinc gluconate and stirring evenly until completely dissolved to obtain a mixed solution; (2) Take the mixed solution obtained in step (1), add the remaining water to make up the volume, and obtain the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor.

5. The method according to claim 4, characterized in that: The temperature is 293~323K.

6. Use of the hydroxyphosphonic acid-zinc gluconate composite corrosion inhibitor according to claim 1 in the corrosion protection of pipeline steel in an acidic environment rich in petroleum.

7. The use according to claim 6, characterized in that The ratio of the concentration of corrosive liquid in pipeline steel to the concentration of corrosion inhibitor is 1:1.5~2.

8. The use according to claim 6, characterized in that Applicable to hydrogen sulfide corrosive environment.

9. The use according to claim 6, characterized in that The application is to use a compound corrosion inhibitor to form a protective film on the inner surface of the pipeline steel to hinder corrosion in an acidic environment.